A systematic review of lung clearance index in non-cystic fibrosis, non-primary ciliary dyskinesia bronchiectasis. (September 2022) - Hine, Christopher; Desai, Maya; Davies, Jane; Sapey, Elizabeth; Nagakumar, Prasad
Abstract: Background: Non cystic fibrosis, non primary ciliary dyskinesia bronchiectasis (nCFnPCD-BE) results in significant morbidity with few evidence-based treatments. Objective: assessments are required to assess severity and evaluate treatment. Lung clearance index (LCI) measures ventilation inhomogeneity and is a sensitive test of disease in CF; its use in nCFnPCD-BE is unclear. Methods: A systematic review of LCI in nCFnPCD-BE was performed using standard methodology (protocol registered on PROSPERO, University of York). Results: Of 276 records identified, 12 articles, describing 519 adult and paediatric patients in cross-sectional studies were included, addressing several domains. 1: What is the utility of LCI in detecting disease and severity? LCI detected disease in adults, differentiating bronchiectasis from controls (AUC 0.90 to 0.96) and mild from moderate/severe bronchiectasis on CT (AUC 0.73). 2: Does LCI correlate with spirometry and imaging? LCI correlated with spirometry in adult (r = −0.37 to −0.61) and paediatric (r = −0.6) groups, signs of bronchiectasis on CT, and CT scoring systems (modified Reiff). 3: Does LCI relate to subjective scores of severity? In adults, LCI correlated with St. George's Respiratory Questionnaire (r = 0.18) and Bronchiectasis Severity Index (r = 0.45). 4: Does LCI identify response to intervention? LCI did not change in studies examining LCI pre-post intervention (adults treated for exacerbation and undergoing physiotherapy). Overall study quality was variable. Conclusion: Contrary to data in CF, the review did not identify good quality studies defining the role of LCI in children with bronchiectasis. In adults, LCI was a sensitive measure of disease severity and correlated with clinical assessment tools. Highlights: The review summarises studies evaluating LCI in non-CF, non-PCD bronchiectasis . No good quality studies were identified evaluating the role of LCI in children with bronchiectasis . In adults, LCI was a sensitive tool to measure disease severity . In adults, LCI also correlated with several clinical assessment tools .